Biphasic Synergistic Gel Materials with Switchable Mechanics and Self‐Healing Capacity. Issue 43 (18th September 2017) - Zhao, Ziguang; Liu, Yuxia; Zhang, Kangjun; Zhuo, Shuyun; Fang, Ruochen; Zhang, Jianqi; Jiang, Lei; Liu, Mingjie
Abstract: A fabrication strategy for biphasic gels is reported, which incorporates high‐internal‐phase emulsions. Closely packed micro‐inclusions within the elastic hydrogel matrix greatly improve the mechanical properties of the materials. The materials exhibit excellent switchable mechanics and shape‐memory performance because of the switchable micro‐ inclusions that are incorporated into the hydrogel matrix. The produced materials demonstrated a self‐healing capacity that originates from the noncovalent effect of the biphasic heteronetwork. The aforementioned characteristics suggest that the biphasic gels may serve as ideal composite gel materials with validity in a variety of applications, such as soft actuators, flexible devices, and biological materials. Abstract : It's morphin' time : Closely packed switchable micro‐inclusions in a hydrogel matrix produce biphasic synergistic gel materials with switchable mechanics, self‐healing capacity, and shape‐memory properties.